Citra Universitas dan Bauran Pemasaran Islam terhadap Keputusan Mendaftar di Perguruan Tinggi - Nurul Iman Maulana; Budi Sukardi (https://jurnal.binamandiri.ac.id/, 2026)
This study was motivated by the low number of student enrollments at STEBIS Bina Mandiri in 2023, which reached only 274 students—far below the target of 500—despite various traditional promotional strategies. The research aims to examine the influence of institutional image and elements of the Islamic marketing mix—including fair pricing, Islamic environment, ethical promotion, and human resource quality—on students' enrollment decisions. Using a quantitative approach with a causal design, the study involved 247 active students as the population, with samples selected purposively using the Slovin formula. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that institutional image and Islamic campus environment have a positive and significant influence on enrollment decisions, while fair pricing, ethical promotion, and human resources do not show significant effects. These findings indicate that institutional reputation and the Islamic atmosphere of the campus are key factors in attracting prospective students.